URBAN STUDENTS’ READING COMPREHENSION ACHIEVEMENT: IMPLICATIONS OF ATTITUDE, MOTIVATION, AND PARENTAL INVOLVEMENT - Welly Ardiansyah; Murwani Ujihanti; Nurul Aryanti (ANGLO-SAXON: Jurnal Ilmiah Program Studi Pendidikan Bahasa Inggris, 2020)
The reason why the writers conducted the research is to know the correlations among reading attitude, and motivation of urban students, and parental involvement towards their reading comprehension achievement of four private polytechnics in Palembang 2018/2019. In conducting the research, the writers used the method of quantitative-correlation. The sample was 99 students and the random sampling method was used.  All the data were analyzed with Multiple Regression. The instrument to collect data in this research is the reading comprehension test comprising 40 questions in terms of multiple choices. The results show that (1) reading attitude has a positive influence towards reading comprehension achievement in which t1= 2.596, p-value = 0.011/2 = 0.0055 0.05, (2) reading motivation has a positive influence towards reading comprehension achievement in which t2= 4.658, p-value = 0.000/2 = 0 0.05, (3) parental involvement significantly influences students’ reading comprehension achievement in which t3= 6.21, p-value = 0.000/2 = 0 0.05, and (4) FCal is 31.189, p-value = 0.000 0.05 which imply that students’ reading attitude, students’ reading motivation, and parental involvement positively affect students’ reading comprehension achievement.